2014
DOI: 10.1186/2050-6511-15-32
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported adverse drug reactions and their influence on highly active antiretroviral therapy in HIV infected patients: a cross sectional study

Abstract: BackgroundPatients on antiretroviral therapy have higher risk of developing adverse drug reactions (ADRs). The impact of ADRs on treatment adherence, treatment outcomes and future treatment options is quiet considerable. Thus, the purpose of this study was to describe the common self-reported ADRs and their impact on antiretroviral treatment.MethodsCross-sectional study was conducted at antiretroviral therapy (ART) clinic of Gondar University Hospital. Semi-structured interview questionnaire was used to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 20 publications
6
31
1
2
Order By: Relevance
“…Clearly, the issue of the relationship between occurrence of adverse drug events and HAART modification is an extremely important one that deserves further concerted study across several countries and with a larger number of patients, especially considering the fact that HIV has now become a chronic condition, with patients likely to be on life-long therapy. In addition, the proportion of patients experiencing an adverse drug event before therapy modification in this study is similar to the proportions found in studies by Padua et al in Brazil [ 35 ] and Tadesse et al in Ethiopia [ 37 ], which indicated that 56.1 and 53.8 %, respectively, of patients who modified to another therapy self-reported at least one adverse drug reaction [ 35 , 37 ]. A similar case–control study in Ethiopia, however, showed that as high as 85.7 % of patients on HAART had changed therapy [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…Clearly, the issue of the relationship between occurrence of adverse drug events and HAART modification is an extremely important one that deserves further concerted study across several countries and with a larger number of patients, especially considering the fact that HIV has now become a chronic condition, with patients likely to be on life-long therapy. In addition, the proportion of patients experiencing an adverse drug event before therapy modification in this study is similar to the proportions found in studies by Padua et al in Brazil [ 35 ] and Tadesse et al in Ethiopia [ 37 ], which indicated that 56.1 and 53.8 %, respectively, of patients who modified to another therapy self-reported at least one adverse drug reaction [ 35 , 37 ]. A similar case–control study in Ethiopia, however, showed that as high as 85.7 % of patients on HAART had changed therapy [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study 62% of the patients experienced side effects since they started using ARVs. These findings compare well with the findings of Tadesse et al (2014) that 89.8% of the study participants experienced at least one adverse drug reaction. A study by Masenyetse et al (2015) established that 37% of the patients on Highly active antiretroviral drugs experienced adverse drug reactions.…”
Section: Side Effects Experienced By Hiv Positive Patients On Haartsupporting
confidence: 90%
“…To our knowledge, only a few retrospective studies have attempted to identify the type and frequency of ADRs in Ethiopian adult patients receiving ART [10,11], and given the poor documentation of ADRs in patients' medical charts, ADRs are underreported. In addition, the impact of ADRs on treatment outcomes (body mass index [BMI] and CD4 count) has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%